Lipopeptides from Bacillus and Paenibacillus spp.: A Gold Mine of Antibiotic Candidates. Issue 1 (28th May 2014) - Cochrane, Stephen A.; Vederas, John C.
Abstract: The emergence of multidrug‐resistant bacteria has placed a strain on health care systems and highlighted the need for new classes of antibiotics. Bacterial lipopeptides are secondary metabolites, generally produced by nonribosomal peptide synthetases that often exhibit broad‐spectrum antimicrobial activity. Only two new structural types of antibiotics have entered the market in the last 40 years, linezolid and the bacterial lipopeptide daptomycin. A wide variety of bacteria produce lipopeptides, however Bacillus and Paenibacillus spp. in particular have yielded several potent antimicrobial lipopeptides. Many of the lipopeptides produced by these bacteria have been known for decades and represent a potential gold mine of antibiotic candidates. This list includes the polymyxins, octapeptins, polypeptins, iturins, surfactins, fengycins, fusaricidins, and tridecaptins, as well as some novel examples, including the kurstakins. These lipopeptides have a wide variety of activities, ranging from antibacterial and antifungal, to anticancer and antiviral. This review presents a reasonably comprehensive list of each class of lipopeptide and their known homologues. Emphasis has been placed on their antimicrobial activities, as well other potential applications for this interesting class of substances.